FGF-mediated establishment of left-right asymmetry requires Rab7 function in the dorsal mesoderm in Xenopus - Kreis, Jennifer; Camuto, Celine Marie; Elsner, Carolin Charlotte; Vogel, Sebastian; Vick, Philipp (Frontiers in Cell and Developmental Biology, 2022)
Gastrulation denotes a very important developmental process, which includes significant structural tissue rearrangements and patterning events that shape the emerging vertebrate organism. At the end of gastrulation, the three body axes are spatially defined while the left-right axis still lacks any molecular or morphological polarity. In most vertebrates, this is established during neurulation by a symmetry breaking LR organizer. However, this mesoderm-derived structure depends on proper induction and specification of the mesoderm, which in turn requires involvement of several signaling pathways. Endocytosis and the endosomal machinery offer manifold platforms for intracellular pathway regulation, especially late endosomes claim increasing attention. The late endosomal regulator Rab7 has been linked to mesoderm specification during gastrulation. Distinct axial defects due to compromised dorsal mesoderm development in rab7-deficient Xenopus embryos suggested a requirement of Rab7 for FGF-dependent mesoderm patterning and LR asymmetry. Here we specifically addressed such a role of Rab7, demonstrating a functional requirement for LR organizer development and symmetry breakage. Using different FGF/MAPK pathway components we show that Rab7 participates in dorsal mesoderm patterning. We suggest a hierarchical classification of Rab7 upstream of MAPK-dependent mesoderm specification, most probably at the level of the small GTPase Ras. Thus, this study affords an insight on how the Rab7-regulated endosomal machinery could participate in signal transduction to enable correct mesoderm specification and left-right asymmetry.